Effects of targeted hydration on risk of major adverse renal and cardiac events: a systematic review and meta-analysis of randomized controlled trials. (25th November 2020) - Guo, Z; Lei, L; Liu, J; Song, F; He, Y; Chen, S; Sun, G; Liu, B; Liu, L; Chen, G; Xue, Y; Huang, H; et al.
Abstract: Background: Inconsistent results have been published that have evaluated the preventive effect of targeted hydration in major adverse renal and cardiac events among patients exposed to contrast agents. Methods: Online databases were searched up to October, 2019, for randomized controlled trials (RCTs). The primary outcome was the incidence of contrast-induced acute kidney injury (CI-AKI), and the secondary outcomes were all-cause in-hospital mortality, all-cause long-term mortality, requirement for dialysis, acute pulmonary edema and stroke/transient ischemic attack (TIA). Results: 9 high quality trials were identified including 2424 patients. Overall, compared with general hydration, targeted hydration significantly reduced the incidence of CI-AKI by 58% (RR 0.42; 95% CI: 0.33–0.54, p<0.01), the requirement for dialysis by 68% (RR 0.32, 95% CI: 0.17–0.62, p<0.01) and the all-cause long-term mortality by 55% (RR 0.45; 95% CI: 0.26–0.76, p<0.01). The effect on all-cause in-hospital mortality was not statistically significant. The effect on acute pulmonary edema and stroke/TIA also showed no difference between two groups (RR: 0.54, 95% CI: 0.28–1.03, p=0.18; RR: 0.61, 95% CI: 0.14–2.61, p=0.49, respectively). Trial sequential analysis confirmed that an additional 3900 study participants would need to be recruited to demonstrate a statistically significant improvement for all-cause in-hospital mortality. Conclusions: Targeted hydration likely reduces the incidence of CI-AKI, dialysis and all-cause long-term mortality in patients exposed to contrast agents. However, further independent high-quality RCTs should elucidate the effectiveness and safety of this prophylactic strategy in interventional cardiology. Funding Acknowledgement: Type of funding source: None